2021
DOI: 10.1093/europace/euab107
|View full text |Cite
|
Sign up to set email alerts
|

Proximity to the descending aorta predicts regional fibrosis in the adjacent left atrial wall: aetiopathogenic and prognostic implications

Abstract: Aims Left atrial (LA) fibrosis is present in patients with atrial fibrillation (AF) and can be visualized by magnetic resonance imaging with late gadolinium enhancement (LGE-MRI). Previous studies have shown that LA fibrosis is not randomly distributed, being more frequent in the area adjacent to the descending aorta (DAo). The objective of this study is to analyse the relationship between fibrosis in the atrial area adjacent to the DAo and the distance to it, as well as the prognostic implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…In contrast, both the Utah- and IIR>1.20 methods most frequently detect LGE at the left posterior LA adjacent to the descending aorta, which is consistent with previous reports [17, 24, 13]. Caixal et al demonstrated that the spatial proximity of posterior LA-wall to the descending aorta determines the degree of LGE in this region [24]. In a subset of 16 patients, these authors reported reduction of bipolar voltages and CV values in LGE-areas at left posterior LA.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, both the Utah- and IIR>1.20 methods most frequently detect LGE at the left posterior LA adjacent to the descending aorta, which is consistent with previous reports [17, 24, 13]. Caixal et al demonstrated that the spatial proximity of posterior LA-wall to the descending aorta determines the degree of LGE in this region [24]. In a subset of 16 patients, these authors reported reduction of bipolar voltages and CV values in LGE-areas at left posterior LA.…”
Section: Discussionsupporting
confidence: 92%
“… 17 Interestingly, the close anatomical relationship between these areas and the descending aorta has been recently claimed to potentially contribute to fibrosis accumulation by means of continuous and repetitive microtrauma. 28 Right atrial fibrosis localization had not been systematically assessed. By mean of rough visual inspection, Akoum and coworkers suggested that the most affected areas were the septum, superior and inferior peri‐cava veins and posterior venous wall.…”
Section: Discussionmentioning
confidence: 99%
“…20 Recently, the extent of atrial fibrosis in this region was demonstrated to be inversely correlated with the distance between the DA and the LA. 21 Our study shows that blood flow even outside the atrium seems to Abbreviations: CI, confidence interval; DA, descending aorta; LIPV, left inferior pulmonary vein; TTI, time-to-isolation.…”
Section: Impact Of Intra and Extra-atrial Blood Flow On The Cbmentioning
confidence: 60%